(untitled) (Progressive Agriculture, 2020)
An experiment has been conducted to observed the disease severity of late blight of potato in the different weather parameters viz., air temperature, soil temperature, dew points, percent relative humidity and period of sunshine. The experiment was conducted in the Net-house, Department of Plant Pathology, Bangladesh Agricultural University (BAU), Mymensingh during July 2016 to November 2017. Weather data were collected on daily basis from BAU weather station during the experimental period. A significant role of weather parameters was detected in disease development and disease progress. Temperature was strongly linked with the late blight infection in potato. From 15 December, 2016 to 12 January, 2017 air temperature was ranged from 21.00-23.50°C and soil temperature was ranged from 19.00-22.00°C, and this range late blight incidence was not detected in the potato plant. From 13-14 January air and soil temperature suddenly decreased 2°C and from next day again increased the temperature as well as starting late blight disease symptoms. It was observed that dew point and percent relative humidity have a big role on late blight disease severity of potato. In 13-14 January, 2017 dew point decreased from 14°C to 8°C and Percent RH decreased from 80% to 51%. From 14 January, 2017, disease symptoms were observed in potato leaves and rapidly increased. Thus, late blight of potato disease may respond to the variation of temperature, dew point and relative humidity. Progressive Agriculture 31 (2): 74-80, 2020